GENOTOXICIDADE E MUTAGENICIDADE DO BIOCIDA ANTI -INCRUSTANTE CLOROTALONIL NA ESPÉCIE Micropogonias furnieri, Desmarest, 1823. - CASTRO, Muryllo Santos (2018)
The biofouling process consists of the installation and growth of marine organisms on submerged or semi submerged surfaces in the water, and is considered one of the great problems related to navigation and maintenance of port structures. The use of antifouling paints is the main way to combat these fouling, however, some of the active principles of current formulations cause adverse effects to non- target organisms. The study of biomarkers in organisms exposed to xenobiotic agents is of great importance for Ecotoxicology, especially in the identification of substances with genotoxic potential. The objective of this work was to evaluate the effects of the anti- fouling chlorothalonil on the DNA of fish, using as a test organism the M. furnieri estuarine species. The juveniles were collected in the municipality of Raposa - Ma and kept in the Laboratory of Ecotoxicology (LabEcotox) of the Federal University of Maranhão, where they were acclimated for 11 days in PVC tanks with recirculation system (mechanical and biologica l filtration) temperature 25º ± 1º C , salinity 20 g / kg and photoperiod (12 / 12h), receiving feed (fresh prawns) ad libitum. At the end of the acclimation period, the fish were separated into four experimental groups. In each group, 20 individuals were injected intraperitoneally with 1μL / g solutio n containing: 1) Negative control - the vehicle consisting of physiological solution and DMSO (90 : 1, v: v); 2) Positive Control -cyclophosphamide (50 mg / kg); 3) 0.35 μg / μL and 4) 3.5 μg / μL chlorothalonil. After 96 hours of injections, subjects from each treatment were anesthetized with eugenol and had blood collected by gill artery puncture for the tests of comet, micronucleus and nuclear anomalies. In general, both doses of chlorothalonil were able to increase the frequencies of DNA damage, micron uclei and nuclear abnormalities (budding, apoptotic and bilobed fragments), indicating that the doses of 0.35 and 3.5 μg / μL have a high potential genotoxic and mutagenic to M. furnieri species.